2022
DOI: 10.3389/fpls.2022.832246
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrate Transporter MtNPF6.8 Is a Master Sensor of Nitrate Signal in the Primary Root Tip of Medicago truncatula

Abstract: Nitrate is not only an essential nutrient for plants, but also a signal involved in plant development. We have previously shown in the model legume Medicago truncatula, that the nitrate signal, which restricts primary root growth, is mediated by MtNPF6.8, a nitrate transporter. Nitrate signal also induces changes in reactive oxygen species accumulation in the root tip due to changes in cell wall peroxidase (PODs) activity. Thus, it was interesting to determine the importance of the role of MtNPF6.8 in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The authors found a maize orthologue of AtUPBEAT1 transcription factor to be responsible for regulating ROS levels by repressing the expression of a POD gene (Zm00001d024119) in a similar fashion to what was described in Arabidopsis, suggesting the existence of an evolutionarily conserved signalling module common to both monocots and eudicots(Trevisan et al, 2019;Tsukagoshi et al, 2010). Accordingly, in M. truncatula, the orthologue of AtUPBEAT1, MtUPBEAT1, was recently found to be downregulated in response to 5 mM NO 3 − treatment(Zang et al, 2022).In M. truncatula, the NO 3 − transporter MtNPF1.7 controls ROS homoeostasis in the primary root tip and promote cell elongation through an increased RBOH activity(Zhang et al, 2014). A link between ROS accumulation and NO 3 − availability was proposed although conclusive evidence was lacking.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The authors found a maize orthologue of AtUPBEAT1 transcription factor to be responsible for regulating ROS levels by repressing the expression of a POD gene (Zm00001d024119) in a similar fashion to what was described in Arabidopsis, suggesting the existence of an evolutionarily conserved signalling module common to both monocots and eudicots(Trevisan et al, 2019;Tsukagoshi et al, 2010). Accordingly, in M. truncatula, the orthologue of AtUPBEAT1, MtUPBEAT1, was recently found to be downregulated in response to 5 mM NO 3 − treatment(Zang et al, 2022).In M. truncatula, the NO 3 − transporter MtNPF1.7 controls ROS homoeostasis in the primary root tip and promote cell elongation through an increased RBOH activity(Zhang et al, 2014). A link between ROS accumulation and NO 3 − availability was proposed although conclusive evidence was lacking.…”
mentioning
confidence: 62%
“…In the following sections, we focus specifically on their roles in regulating the root system architecture in response to nutrient stress. Interestingly, no change in ROS accumulation or POD activity was observed in the primary root tip of the mutant npf6.8 deficient in the NO 3 − transporter MtNPF6.8 that has lost the sensitivity to NO 3 − (Zang et al, 2022). It is noteworthy that such a mechanism does not occur in lateral roots, in which growth rate is enhanced in the presence of NO 3 − .…”
Section: Ros Signal Transduction Through Protein Oxidationmentioning
confidence: 95%
“…For this aim, sequences of genes determined in our previous studies as being nitrate-inducible in M. truncatula roots at early stages of development [ 9 , 20 , 21 , 22 ] were used to browse the P. sativum genome database ( (accessed on 8 June 2022)) and search for sequences of their orthologs in this species. Chosen genes were: MtNR1 (nitrate reductase), MtGS1 (cytosolic glutamine synthetase), MtGS2 (plastidic glutamine synthetase), MtASNS (asparagine synthetase), MtNPF6 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present work we studied the regulation of PsNPF6.4 , an ortholog of M. truncatula nitrate transporter MtNPF6.7 , identified in one of our previous works as a nitrate-inducible gene [ 22 ]. In here, PsNPF6.4 expression was not detected in young (2-day-old) seedlings in all conditions and in 12-day-old seedling in the absence of nitrate, but it was slightly detected in 5-day-old seedlings in the absence of nitrate ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation